Groundwater recharge and age‐depth profiles of intensively exploited groundwater resources in northwest India. Issue 18 (22nd September 2015) - Lapworth, D. J.; MacDonald, A. M.; Krishan, G.; Rao, M. S.; Gooddy, D. C.; Darling, W. G.
Abstract Intensive irrigation in northwest India has led to growing concerns over the sustainability of current and future groundwater abstraction. Environmental tracers and measurements of groundwater residence times can help quantify the renewal processes. Results from 16 paired locations show the interquartile ranges for residence times in shallow alluvial groundwater (8–50 m deep) to be 1–50 years and significantly less than those from deeper groundwater (76–160 m deep) at 40–170 years. The widespread occurrence of modern tracers in deep groundwater (>60% of sites had >10% modern recharge) suggests that there is low regional aquifer anisotropy and that deep aquifers are recharged by a significant component of recent recharge via vertical leakage. Stable isotope and noble gas results at all depths conform to modern meteoric sources and annual average temperatures, with no evidence of significant regional recharge from canal leakage in this study area close to the Himalayas.